ЗМІНА ПАРАДИГМИ ПРОДАЖУ БАНКІВСЬКИХ ПОСЛУГ В УМОВАХ РОЗВИТКУ ЦИФРОВИХ КАНАЛІВ ДИСТРИБУЦІЇ (Світ фінансів, 2017)
Кириленко С. В. Зміна парадигми продажу банківських послуг в умовах розвитку цифрових каналів дистрибуції. Розглянуто теоретичні та практичні аспекти продажу банківських послуг для фізичних осіб. Проаналізовано вплив сучасних цифрових технологій на специфіку дистрибуції роздрібних банківських продуктів, пов’язану із проникненням інформаційних технологій у фінансовий сектор. Наведено практичні приклади та проаналізовано досвід розвитку роздрібного банківського бізнесу в окремих розвинутих країнах Заходу. Запропоновано низку методичних рекомендацій щодо імплементації зарубіжного досвіду у вітчизняний банківський сектор. Визначено напрямки трансформації моделі обслуговування клієнтів в контексті переходу до цифрових каналів обслуговування. Кириленко С. В Смена парадигмы продажи банковских услуг в условиях развития цифровых каналов дистрибьюции. Рассмотрены теоретические и практические аспекты продажи банковских услуг для физических лиц. Проанализировано влияние современных цифровых технологий на специфику дистрибьюции розничных банковских продуктов, связанную с проникновением информационных технологий в финансовый сектор. Приведены практические примеры и проанализирован опыт развития розничного банковского бизнеса в отдельных развитых странах Запада. Предложены методические рекомендации, касающиеся имплементации зарубежного опыта в отечественный банковский сектор. Определены направления трансформации модели обслуживания клиентов в контексте перехода на цифровые каналы обслуживания. Kyrylenko S. Change of banking services sales paradigm in terms of digital distribution channels.  Introduction. This article contains analysis of the impact of modern digital technology to the distribution of retail banking products, practical examples and experience of the retail banking business in developed countries, and number of guidelines for the implementation of international experience in the domestic banking sector.With the development of information technology, accompanied by global penetration of mobile Internet access and digital services, changes occur in the provision of financial services. The implantation of new technologies requires banks to review the methodology and process of banking services according to changes in customer behavior.Purposes. The aim of this article is to determine the changes in the retail banking business with the spread of information technology, systematization of modern trends in banking services with the use of remote sales channels, analyze their impact on the provision of retail banking services and provide practical recommendations on the implementation experience of banks.Conclusion. Switching banks in the digital age in practice means a change in the banking infrastructure:– Creating a fully digital products that do not require paper documents.– The tight integration of banking software systems with CRM-systems and software that allows to track client activity, analyze the information and build forecasts for the future customer needs.– Simplification of banking services and products along with provision of non-banking services.